Magnetocaloric effect in low cost MnNiSi-based alloys with Fe and Al doping - Ong, Rong (2018)
Magnetic materials that have magnetocaloric effects at room temperature are generating huge interest because of their potential to replace the conventional gas compression cooling technology. Magnetic cooling has various significant advantages such as environmentally friendly, energy efficient, generates lesser noise and can be more compact as working material is in solid form. Currently, rare earth based materials such as Gadolinium-based alloys are ideal candidates for magnetic cooling because of their strong magnetocaloric properties at room temperature. However, they are limited, expensive and have low corrosion resistance. In order to commercialise magnetic cooling, there is a need to find alternative alloys which are cheaper, readily available and have comparable magnetocaloric properties. This project focuses on the magnetocaloric effect in low cost MnNiSi-based alloys with Fe and Al doping. The composition of Mn0.5Fe0.5NiSi1-xAlx alloy with x = 0.04, 0.05 and 0.06 was investigated for its magnetocaloric properties. Experiments such as arc melting and heat treatment were conducted to process the alloy. Thereafter, various characterisations including room temperature magnetization measurement using Vibrating Sample Magnetometer (VSM) and structural characterization such as X-ray Diffraction (XRD), High Temperature XRD, Differential Scanning Calorimetry (DSC), and Energy-dispersive X-ray Spectroscopy (EDS) were conducted to obtain more information on the Mn0.5Fe0.5NiSi1-xAlx alloy magnetic properties.